Chloride cotransport in the membrane of earthworm body wall muscles - Volkov, E M; Nurullin, L F; Nikolsky, E; Krůsek, J; Vyskocil, F (Physiological research, 2003)
The resting membrane potential (V(m)) of isolated somatic longitudinal muscles of the earthworm Lumbricus terrestris was studied by glass microelectrodes. The inhibition of chloride permeability by low pH did not affect V(m) of the muscle fibers in isolated somatic longitudinal muscles of the earthworm Lumbricus terrestris which was -48.7 mV (inside negative) at pH 7.3 and -49.1 at pH 5.6. On the other hand, bathing the muscles in Cl(-) and Na(+)-free solutions, or application of the chloride transporter inhibitor furosemide and Na(+)-K(+)-ATPase inhibitor ouabain depolarized the V(m) by 3-5 mV. The effects of a Cl(-) -free solution and ouabain were not additive. This demonstrates relatively small contribution of equilibrium potential for Cl(-) to the resting membrane potential and electrogenic effect of Na(+)K(+)-ATPase which is dependent on the supply of Na(+)(i) ions by furosemide-sensitive and Cl(-)(e)- and Na(+)(e)-dependent electroneutral transport (most probably Na(+)K(+)Cl(-) cotransport).
Keywords: osmolární koncentrace; membránové potenciály; Electrophysiology; Potassium; In Vitro Techniques; iontový transport; draslík; koncentrace vodíkových iontů; Sodium Potassium Chloride Symporter Inhibitors; Furosemide; chloridy; elektrofyziologie; kosterní svalová vlákna; techniky in vitro; sodíko-draslíková ATPasa; Muscles; ouabain; Membrane Potentials; Osmolar Concentration; sodík-draslík-chloridové symportéry; Ouabain; Ion Transport; Oligochaeta; Chlorides; Muscle Fibers, Skeletal; zvířata; Hydrogen-Ion Concentration; inhibitory Na-K-Cl symportérů; svaly; sodík; Sodium-Potassium-Exchanging ATPase; Sodium-Potassium-Chloride Symporters; furosemid; Sodium; Animals